Double-size texturisation and biphasic calcium phosphate coatings obtained via laser technologies for bioactive zirconia dental implant surfaces - Pereira, L. M. (2024)
Commercial zirconia dental implants have a well stablished surface treatment to boost osseointegration based on grit-blasting and acid-etching procedures. Nevertheless, research studies aim to use laser surface texturing (LST) as an eco-substitute for commercial procedure. Moreover, LST allows the creation of designed patterns such as aligned grooves, cross-linked and spots. Laser technology also allows the bioactive coatings treatment, consisting in surface modification. This work designed three patterns in zirconia via LST and biphasic calcium phosphate 70HaP/30β-TCP coatings were laser treated. Analyses were performed via SEM, profilometry, XRD, and EDS to evaluate the quality of laser textures and bioactive coatings. Three different textures were successfully obtained. The cross-linked groove texture with squared ridges of 100 μm, groove width of 30 μm and 100 μm of depth. The micropit texture with aligned spots with 35 μm diameter, spaced by 15 μm and 30 μm depth. The third texture overlaps the previous textures, resulting in six spots per squared ridge. Laser treatment was found to be an expedited process for 70HaP/30β-TCP coating thermal treatment, resulting in a shaped and smooth coating.